Selective microstructure-size filters for non-invasive quantitative imaging by mag- netic resonance - Zwick, Analía Elizabeth (2021)
Extracting quantitative microstructure information of living tissue by non-invasive imaging is an outstandingchallenge for understanding disease mechanisms and allowing early stage diagnosis of pathologies. Magnetic Reso-nance Imaging (MRI) is a promising and widely used technique to pursue this goal, but still provides low resolutionto reveal microstructure details [1]. We here report on a method to produce images of filtered microstructure-sizesbased on selective probing of nuclear-spin dephasing induced by the molecular diffusion within specific tissue-compartments [2]. The microstructure-size filter relies on suitable dynamical control of nuclear spins that sensemagnetization decay-shifts rather than the commonly used spin-echo decay-rates. The feasibility and performanceof the method are illustrated with proof-of-principle experiments and simulations on typical size-distributions ofwhite-matter in the mouse brain [3]. These results show that spin-echo decay-shifts can be a new MRI paradigmto advance towards unravelling diagnostic information based on microstructure parameters that characterize bio-logical tissues.